Existence and Uniqueness of Generalized Solutions to a Telegraph Equation with an Integral Boundary Condition via Galerkin's Method - Assia Guezane-Lakoud; Jaydev Dabas; Dhirendra Bahuguna (International Journal of Mathematics and Mathematical Sciences)
We consider a telegraph equation with nonlocal boundary conditions, and using the application of Galerkin's method we established the existence and uniqueness of a generalized solution.